Potensi peninggalan arkeologi Benteng Orange di Gorontalo Utara sebagai sumber belajar sejarah lokal (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Orange Fort in North Gorontalo is an archaeological heritage site with high historical significance, yet its educational potential has not been fully utilized. This study aims to examine the fort’s potential as a local history learning resource and formulate effective strategies for its integration into senior high school history education. Using a literature review method, this research analyzed scholarly works on historical heritage, history pedagogy, and the use of cultural sites in learning. The analysis focused on the relevance of the fort’s historical content to the history curriculum and its applicability in classroom practices. The findings reveal that Orange Fort can be used through various pedagogical models, including field trips, digital learning media development, and student research projects. Its use enriches local historical content, enhances students’ historical awareness, strengthens critical thinking skills, and fosters nationalism. However, sustainable implementation requires proper conservation, site management, and curriculum alignment. Therefore, collaboration among government agencies, educators, academics, and local communities is essential. This study contributes to the discourse on innovative and contextual history education by emphasizing the importance of integrating cultural heritage sites into formal learning to promote meaningful and sustainable local history education.
Keywords: Cultural heritage; local history learning; Orange Fort; placebased education